HASIL TANAMAN SELADA (Lactuca sativa L.) PADA KOMPOSISI MEDIUM BERBEDA YANG DIPUPUK DENGAN UREA DALAM SISTEM BUDIDAYA TERAPUNG LAHAN RAWA GAMBUT - Wawan Wawan; Fikrawati Fikrawati (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2021)
The cultivation of lettuce floating system peat swamps with different media compositions given with urea has never been studied. The aim of this study was to determine the interaction between medium composition and the dose of urea which produces best lettuce (Lactuca sativa L.) growth and yield on peat swamp floating cultivation. The research used 4×4 factorial in completely randomized design with two factors. First factor was type of medium composition consists of four levels, 70% peat:5% Inceptisol:20% chicken manure fertilizer:5% OPEFB ash; 60% peat:15% Inceptisol:20% chicken manure fertilizer:5% OPEFB ash; 50% peat:25% Inceptisol:20% chicken manure fertilizer:5% OPEFB ash); 40% peat:35% Inceptisol:20% chicken manure fertilizer:5% OPEFB ash. The second factor was urea dose consists of fout levels, without urea), 2 g per polybag; 4 g per polybag, 6 g per polybag. The results showed that the interaction between the medium composition and the dose of urea had an effect on the yield of lettuce. The composition of 50% peat:25% Inceptisol:20% chicken manure fertilizer:5% OPEFB ash medium produced the best lettuce growth when fertilized with a dose of 2 g per polybag urea.